Expanded‐Ring N‐Heterocyclic Carbenes for the Stabilization of Highly Electrophilic Gold(I) Cations. Issue 50 (21st October 2014) - Phillips, Nicholas; Dodson, Tristan; Tirfoin, Rémi; Bates, Joshua I.; Aldridge, Simon
Abstract Strategies for the synthesis of highly electrophilic AuI complexes from either hydride‐ or chloride‐containing precursors have been investigated by employing sterically encumbered Dipp‐substituted expanded‐ring NHCs (Dipp=2, 6‐iPr2C6H3). Thus, complexes of the type (NHC)AuH have been synthesised (for NHC=6‐Dipp or 7‐Dipp) and shown to feature significantly more electron‐rich hydrides than those based on ancillary imidazolylidene donors. This finding is consistent with the stronger σ‐donor character of these NHCs, and allows for protonation of the hydride ligand. Such chemistry leads to the loss of dihydrogen and to the trapping of the [(NHC)Au]+ fragment within a dinuclear gold cation containing a bridging hydride. Activation of the hydride ligand in (NHC)AuH by B(C6F5)3, by contrast, generates a species (at low temperatures) featuring a [HB(C6F5)3]− fragment with spectroscopic signatures similar to the "free" borate anion. Subsequent rearrangement involves BC bond cleavage and aryl transfer to the carbophilic metal centre. Under halide abstraction conditions utilizing Na[BArf4] (Arf=C6H3(CF3)2‐3, 5), systems of the type [(NHC)AuCl] (NHC=6‐Dipp or 7‐Dipp) generate dinuclear complexes [{(NHC)Au}2(μ‐Cl)]+ that are still electrophilic enough at gold to induce aryl abstraction from the [BArf4]− counterion.